Trends in the age-related incidence of colon and rectal cancers in China, 2005–2015. Issue 7 (July 2021) - Wang, Junyi; Liu, Li; Cai, Yaning; Gao, Yang; Guo, Zhaoyan; Yu, Fangfang; Ping, Zhiguang
Abstract: Background: Recent evidences showed that the incidence of colorectal cancer decreased among older adults, yet this decline didn't appear in adults younger than 50 years. Our aim was to evaluate age-related incidence trends of colon and rectal cancers in China during 2005-2015. Methods: A retrospective study of colon and rectal cancers was conducted using population-based data from the Chinese Cancer Registry Annual Report . Age at diagnosis was analyzed in five sub-groups (0–19, 20–34, 35–49, 50–64 and 65 years). Data including new cases, incidence, and age-standardized rates (ASRs) were classified by sex and area. Temporal trends of ASRs were determined with Joinpoint regression analysis. Results: From 2005 to 2015, colon cancer incidence decreased by -2.2% (95%CI: -3.1, -1.3) per year. A more steady decrease was seen in rectal cancer with AAPC of -0.9% (95%CI: -1.4, -0.4). Stratified by age at diagnosis, incidence trends followed a similar pattern, without age-related disparity. Females showed pronounced declines relative to males. The exception was that rural individuals showed opposite increasing trends, with 2.7% of AAPCs for colon cancer and 2.0% for rectal cancer. Conclusion: A slight decline was observed in colon and rectal cancers during 2005–2015, regardless of age at diagnosis.